Rosa Liebe unterm roten Stern : zur Lage des Lesben und Schwulen in Osteuropa. - Hauer, Gudrun; Krickler, Kurt; Schmutzer, Dieter; Hauberger, Doris; Pankratz, Helga; Vonk, Hans (Wien : Homosexuelle Initiative (HOSI) Wien, 1984)
Fonds Suzan Daniel (FSD)
Fonds Suzan Daniel (FSD)F/97/008
Duits
Monografie